Large lateral photovoltaic effect in a-Si:H/c-Si p–i–n structure with the aid of bias voltage. (6th November 2015) - Qiao, Shuang; Liu, Yanan; Liu, Jihong; Chen, Jianhui; Yan, Guoying; Wang, Shufang; Fu, Guangsheng
Abstract: In this paper, for the first time, we report a significant enhancement of the lateral photovoltaic effect (LPE) in a hydrogenated amorphous silicon/monocrystalline Si (a-Si:H/c-Si) p–i–n structure via the application of a transverse bias voltage. The position sensitivity of this a-Si:H/c-Si p–i–n structure increased linearly with both laser power and wavelength, and the position sensitivity reached a minimum of 809 mV/mm for a 980 nm laser, which was approximately 43 times larger than that without the bias voltage. Moreover, this structure exhibited good linearity with nonlinearity of no more than 3%. We attribute this greatly improved LPE to the enhanced Schottky-barrier-dependent transmitted possibility of photo-generated holes.